2006
DOI: 10.1128/jvi.02119-05
|View full text |Cite
|
Sign up to set email alerts
|

Human Leukocyte Antigen B58 Supertype and Human Immunodeficiency Virus Type 1 Infection in Native Africans

Abstract: Human leukocyte antigen (HLA) class I alleles can be grouped into supertypes according to their shared peptide binding properties. We examined alleles of the HLA-B58 supertype (B58s) in treatment-naïve human immunodeficiency virus type 1 (HIV-1)-seropositive Africans (423 Zambians and 202 Rwandans). HLA-B and HLA-C alleles were resolved to four digits by a combination of molecular methods, and their respective associations with outcomes of HIV-1 infection were analyzed by statistical procedures appropriate for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
53
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 32 publications
7
53
1
Order By: Relevance
“…B58s (POR, 0.33; 95% CI, 0.21 to 0.52) was associated with control that was heavily determined by B*57 alleles (POR, 0.11; 95% CI, 0.05 to 0.22). However, neither the strong protective effect observed elsewhere for B*5801 (22,27) nor the strong deleterious effect observed elsewhere for B*5802 (22,23,27) was observed in our study.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…B58s (POR, 0.33; 95% CI, 0.21 to 0.52) was associated with control that was heavily determined by B*57 alleles (POR, 0.11; 95% CI, 0.05 to 0.22). However, neither the strong protective effect observed elsewhere for B*5801 (22,27) nor the strong deleterious effect observed elsewhere for B*5802 (22,23,27) was observed in our study.…”
Section: Resultscontrasting
confidence: 99%
“…Associations between supertypes and HIV-1 outcomes have been demonstrated in previous studies of Caucasians with clade B infection (34,44) and of native Africans with clade A or C infection (23,28). Caucasians in one study showed an unfavorable effect of B7s and a favorable effect of B58s on HIV-1 control (44); in another study, Caucasians with the relatively infrequent B58s, B27s, and B62s supertypes showed enhanced CTL responses, while the more frequent B7s and B44s supertypes were associated with diminished CTL responses (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 This association was not observed in healthy controls carrying the A*02 allele, indicating that the lower count may be related to a locus in LD with the A*02 allele. We identified one published report 14 of an association between the B*5802 allele and higher viral load in HIV-1 subtype C-infected Zambians, although the B*5801-Cw*03 haplotype was associated with lower viral load. Furthermore, an association between the B*58 allele and higher T-cell response in vertically-HIVinfected AA children (predominately females) has been reported.…”
Section: Discussionmentioning
confidence: 93%
“…In contrast to other clades (including clade D), HLA-B*5801 does not appear to place selection pressure on clade A1 TW10. A previous study in Rwanda similarly showed that in clade A1, HLA-B*5703 but not HLA-B*5801 was associated with lower HIV viral loads (30). Therefore, HLA-B*5801 was associated with neither protection nor selection in clade A1 TW10.…”
Section: ϫ7mentioning
confidence: 95%